FENOMENA PANIC BUYING DAN SERVICE CONVENIENCE TERHADAP KEPUTUSAN PEMBELIAN DI KABUPATEN CIAMIS PADA MASA PANDEMI COVID-19 - Rosyadi, Agi; Mandasari, Andina Eka (Buletin Studi Ekonomi; VOLUME.28.NO.01.TAHUN.2023, 2023)
Purchasing decision is a process of consumer selection in choosing alternatives to buy a product or service according to their preferences, this process is of course based on the personal awareness of consumers according to the needs and wants of the consumers themselves.  The purpose of this study is to analyze the influence of panic buying and service convenience on purchasing decisions during the Covid-19 Pandemic in Ciamis Regency. The research approach used is a quantitative approach with explanatory methods, research instruments through questionnaires. The respondents of the study as many as 50 people were the people of Ciamis Regency, especially housewives with a productive age of 25-45 years who often shop at the Yogya Supermarket Department Store Ciamis, a sampling technique with purposive sampling. Data analysis techniques use multiple regression. The results showed that there was a positive and significant influence of panic buying and service convenience on purchasing decisions during the Covid-19 Pandemic in Ciamis Regency .